G123 Use of Non-Prescribed Medicines, Supplements and Therapies by Children with a Chronic Illness and Children with an Acute Injury – a Comparative Mixed-Methods Study in UK. (4th June 2013) - Hurley, M; Gates, J; Ho, J; Gaunt, A; Smyth, A
Abstract : Aims: To quantify, describe and compare non-prescribed agent (NPA) use by children with, and without, chronic illness To explore families' experience and motivations for giving (or not) NPAs Methods: A questionnaire and semi-structured interview study using an explanatory sequential approach. Parents of children attending fracture, cystic fibrosis (CF), haemato-oncology, neurology and children's development clinics were recruited at first attendance during October-December 2011. Children attending fracture clinic with a chronic illness were re-categorised. Quantitative data were analysed using descriptive statistics and group-wise comparisons using chi-squared and unpaired t-tests. Qualitative data, collected from interviews until data saturation, were coded then thematically analysed independently by three researchers. Results: During the study period 664 families attended clinics, 295 completed a questionnaire (response rate 44.4%). Response rates varied by clinic (fracture clinic 33.8%, chronic clinics 57.8%). 60.3% children were male with a mean age of 9.16 years (sd 4.87). Children with a chronic illness were younger ( p < 0.001). Overall prevalence of NPA use was 37.3%. Specific prevalences – 10% fish oils, 16% vitamins, 15% probiotics, less commonly noted included homoeopathy and hyperbaric oxygen. Differences in NPA use between clinics were small (33%-41.6%, p = 0.21). NPA use was not associated with age, gender, or socioeconomic status. 46.3% parents reported having told their doctor about NPA use. Sixteen parents completed an interview, representing all groups. Ten themes were identified, including the parental intention in providing (or withholding) NPAs. Themes describing why parents did, or did not, provide their children with NPAs included a wish to take an active role, trust (in health professionals, or in the remedy of choice) and accessibility of doctors or NPAs. Conclusions: This is the first UK-based study to compare NPA use between children with and without chronic illness, detailing parental motivators. These are complex but relate to intent, trust, and a wish to take an active role in their child's healthcare. The prevalence of NPA use in this study is similar to others. We found no association between NPA use and chronic illness.